Inflammatory myofibroblastic tumor of the prostate after transurethral resection of the prostate with negative expression of anaplastic lymphoma kinase : a case report - Zeng, Jie; He, Rong-Quan; Mo, Wei-Guang; Peng, Zhi-Gang; Ma, Jie; Zhong, Jin-Cai; Mo, Chao-Hua; Qin, Mei-Jiao; Hu, Xiao-Hua (São Paulo Medical Journal, 2018)
CONTEXT: Inflammatory myofibroblastic tumors are a rare type of soft-tissue tumor. Inflammatory myo- fibroblastic tumors are characterized by rearrangements involving the anaplastic lymphoma kinase gene locus on 2p23. CASE REPORT: We report the case of a 67-year-old Chinese male who presented with dysuria and fever. Magnetic resonance imaging showed an irregular prostatic mass with an isointense signal and obscure boundary. Histopathological evaluation showed that the mass consisted mainly of spindle-shaped cells. Immunohistochemical evaluation showed that the tumor cells were negative for anaplastic lymphoma kinase. CONCLUSIONS: Inflammatory myofibroblastic prostate tumors are rare lesions with unclear etiology. The pathological diagnosis is very important.